Seismic performance of ductility classes medium RC beam-column connections with continuous rectangular spiral transverse reinforcements - Azimi, Mohammad Amin (Brazilian Association of Computational Mechanics, 2015)
The seismic performance of RC columns can considerably be improved through the use of continuous spiral reinforcement in terms of ductility and energy dissipation capacity. Since the beamcolumn connections were subjected to brittle failure after earthquakes, the simultaneous application of this method in both beams and columns could greatly improve the seismic behaviour of such connections. In this investigation, a new proposed detail for beam to column connection introduced as “twisted opposing rectangular spiral” was investigated both experimentally and numerically and its seismic performance was verified through comparison with normal rectangular spiral and conventional shear reinforcement systems. In this research, three full scale beam to column connections were first designed according to Eurocode (EC8-04) for Medium ductility classes and then tested by quasi-static cyclic loading suggested by ACI Building Code (ACI 318-08). Finally, numerical methods were hired to validate the experimental results. The results indicated that the ultimate lateral resistance, ductility and energy dissipation capacity of the connection could be improved using the new proposed connection.